The Potential of Decentralized Health Service Delivery in Enhancing the Performance of Primary Health Care Workers in Uganda - Oboi, Emmanuel; Mwesigwa, David; Okuna, Victor (International Journal of Health Sciences, 2026)
Purpose: This study aimed to analyze the potential of decentralized health service delivery in addressing the performance of healthcare workers in Uganda. Methodology: We adopted desk research in which relevant secondary literature was reviewed throughout to identify the link and gaps existing therein. This is a qualitative research method adopted with a view of understanding the complexities of decentralized healthcare service delivery and its impact on Primary Health Care worker performance. Four research questions are asked and answered in line with resource allocation, training, recruitment, and supervision. Findings: The outcomes reveal that decentralized practices may influence healthcare worker performance. We argue that decentralization fosters improved healthcare delivery and worker effectiveness thus highlighting decentralization as a critical strategy for strengthening primary healthcare systems and addressing community-specific health needs in Uganda. Unique Contribution to Theory, Policy and Practice: This study contributes to the strategic shift towards decentralized service delivery, particularly in healthcare, as an empowering tool to local governments and communities, by transferring authority from central administrations as a modus operandi to improved service delivery. It is encouraged that policy makers strengthen strategies that promote decentralization in health service delivery.